A Regional Income Convergence Process in East Java (Indonesia): Do Spatial Dependence and Spatial Regimes Matter? - Lilik Sugiharti, -
East Java has experienced a high level of disparity across regionas, and tend to increase over time, in aaaition, most of the studies on regional income convergence has ignored spatial dependence